Smith, Minnie,2. Minnie Smith interview, July, 1984. - Silk, Hiram (1984)
Minnie Smith discusses Twillingate history and what it was like when she was young. She discusses family history and storied: her father was a police officer in Twillingate for 40 years. She discusses what life was like in Twillingate many years ago, and winter pastimes such as skating on the frozen harbour and society suppers and dances. She discusses Christmas customs: music and church services. She discusses hearing Georgina Stirling sing in church in the 190s. She discusses her husband, the first and only whaling captain in Newfoundland, and stories of his travels and their lives.